(untitled) (Journal of Global Accounting, 2023)
Globally, the sustainability of pension funds is now a concern, from the fear of an inverted pyramid to soaring inflation and until recently, failures of Liability Driven Investments (LDI) an exotic financial instrument hitherto designed to withstand financial uncertainties. Nascent pension funds like the contributory pension scheme will need to rejig its strategies to avert a crisis. In this study, the ratio of Pension Liability to Pension Asset proxied as a measure of pension fund sustainability which is the dependent variable of the study, while Inflation rate was measured with Average rate of returns rate and ratio of Pension Assets to Gross Domestic Product. Using regression to test the data of ten years 2013 to 2022, the result indicates that the inflation rate and average returns rate had a strong and positive but non-significant effect on the sustainability of pension fund (p-values 0.303 and 0.081 > 0.05). This result is a pointer to the fact that the sustainability of the Pension Fund is tied to the performance of the economy and the growth of the pension assets. Managing fund performance by risk diversification is thus recommended for fund managers towards enhancing fund performance. Macroeconomic stabilization as the government should take steps to grow the economy because of the cascading effect on pension sustainability. Policymakers should endeavour to strengthen its supervisory and monitoring roles, prudential laws, and supportive legislation in other to ensure that ensure that pension funds are managed responsibly.